Socio-Spatial Factors Influencing the Location of Economic Enterprises in Obunga Informal Settlement, Kisumu City - Samburu, Peter Maluki (JOOUST, 2020)
The location of economic enterprises forms an essential part of planning as they transform settlements into sustainable nodes of growth and development. However, lack of or inefficient enforcement of planning regulations and guidelines result into uncoordinated development of economic enterprises. As such, this study seeks to understand if informality and growth of economic enterprises obeys any spatial order. The purpose of this study was to investigate the socio-spatial factors influencing the location of economic enterprises in Obunga informal settlement, Kisumu city. The research was guided by the Space Syntax Theory, Systems Theory and Theories of Optimal Location such as the Bid Rent Theory and Gravity Model. It was further guided by cross-sectional survey research design, multi-stage, stratified and purposive sampling techniques. The target population comprised of 211 economic enterprise owners (operators) which included 106 operators ofretail shops, 39, M-pesas, 30 food kiosks and 36 barbershops and salons. The corresponding sample size included 176 economic enterprise operators which included 80 retail shops, 36 M-pesas, 28 food kiosks and 32 barbershops and salons. Qualitative and quantitative data was collected through questionnaires, geo-positioning and onscreen digitization, and literature reviews. The first objective examined the spatial pattern of economic enterprises. Data were analyzed through spatial analysis. Results showed that economic enterprises cluster majorly around street junctions and near other commercial activities. The second objective investigated the relationship between selected aspects of building typology and location of economic enterprises. A multilinear analysis results were presented using a model summary table, Analysis of Variance (ANOVA) regression model was used to test the corresponding hypothesis. Findings indicated a significant relationship between aspects of building typology and location of economic enterprises (F=l0.824, critical value=2.094, a=0.05). This relationship was contributed by: house rent (~=-0.435, p=0.00), construction materials (~=-0.239, p=0.021), cost of building construction (P=-0.209, p=0.049), tenure status (P=-0.96, p=0.375), room size (P=-0.104, p=0.339), building accessibility (P=-0.129, p=0.270) and access to basic amenities (~=-0.07, p=0.095). The third objective determined the influence of circulation space configuration attributes on the location of economic enterprises. Spearman correlation coefficients of circulation space configuration attributes (betweenness, integration, connectivity and mean depth) were determined against the location of economic enterprises. The corresponding hypothesis was tested using multilinear ANOV A regression model. Findings indicated a significant relationship between circulation space configuration attributes with retail shops (F=IS.794), food kiosk (F=34.143) M-pesas: (F=ll.466) and barbershops and salons (F=l 1.539) at F-critical value (2.705) and the p-value=0.000 at a=0.05. Results of R¬square values indicated that circulation space configuration attributes can predict the location of retail shops, food kiosks, M-pesas and barbershops and salons by 41 %, 59.7%, 33.3%, and 33.4% respectively. Betweenness was found to be the best predictor of the location of economic enterprises. Key recommendations included enhancement of street interconnectivity and redesigning of intersections to accommodate more business activity and avoid likely user conflicts, participatory approach and public private partnerships in planning for economic activities, enhancement of the quality of circulation spaces, and recognition of informal settlements' economic enterprises for physical planning.